Dublin 1600-1800 : a study in urban morphogenesis - Burke, Nuala T. (School of Histories and Humanities, 1972)
From the year 1600 Dublin City, for so long cramped behind its medieval walls and towers, began to grow and transform, to expand, and to evolve through two centuries of sustained development into a 'splendid and luxurious capital?. The purpose of this study is to describe, analyse and explain the morphological development of Dublin during this period, from 1600 to the passing of `The Act of Union? in 1800, and to identify and explain influences and agents which determined the form of development. More than anything else it was the final location of central government and administration in Dublin following the domination of the entire island in 1603 which created a sustained demand for residential and for public building, and during the seventeenth and eighteenth centuries development was a response to the changing political, economic and social situation which evolved and which, in 1800, was altered by the Act of Union and its consequences. The year 1800 is a ?watershed? in the development of Dublin comparable to no other in its history. Growth continued after this date but the character of the city, its plan and buildings, gradually changed.
PUBLISHED
Keywords: History; Ireland; Dublin